The Judicial Politics of White Collar Crime - Strader, J. Kelly (1999)
White collar crime cases produce a curious paradox in Supreme Court jurisprudence: in a substantial number of the Court's leading white collar criminal cases, ranging from insider trading to political corruption cases, the liberal justices have voted to affirm convictions, and the conservative justices to reverse them. Even more frequently, these cases have produced strange alliances among the liberals and conservatives, who rarely split into such groupings in non-white collar criminal cases. And it is not merely votes and alliances that change in white collar cases; judicial philosophies, attitudes, and rhetoric transmogrify into a veritable twilight zone of Supreme Court criminal law jurisprudence. The common view of the Court's white collar jurisprudence -- that it is essentially class-based and result-driven -- is a cynical one. This view postulates that the members of the Court alter their positions on criminal justice matters according to subjective reactions to the defendant's social status. From this perspective, legal analysis in white collar cases, which often involves complex issues of statutory interpretation, simply cloaks decisions rooted in personal bias. A close analysis of the cases shows, however, that other variables more likely determine the outcomes in white collar cases. For example, it could be that the types of issues usually raised in the white collar cases (statutory rather than constitutional, substantive rather than procedural), rather than the white collar context itself, determine the voting. Or, it may simply be that conservative justices seek to rein in big federal government, especially in areas involving economic regulation and/or federal intrusion into areas of traditional state responsibility. Finally, the voting may be determined by the justices' views of the very process of criminalization, as applied in the white collar context. With respect to the latter point, the Court rarely addresses questions concerning limitations on criminalization: Do we render acts criminal because they cause harm? If so, what sorts of harm is worthy of criminalization? Professor Strader's suspicion is that the sorts of economic harms produced by white collar crime do not, in the minds of the conservative justices, truly deserve to be criminalized. The liberals, on the other hand, find these harms quite deserving of criminalization, and are willing to rewrite vague, overbroad statutes so that they pass constitutional muster. In this article, Professor Strader suggests that the Court would better serve the criminal justice system by acknowledging that white collar criminalization is appropriate, while declining to rewrite vague and incomprehensible laws, the passage of which was based more often upon political expediency (Congress's desire to get tough on crime ) than upon any reasoned effort to protect society from some sort of identifiable harm